Motion of Particles in Shear Flows Taking into Account Connected Mass (International Journal of Psychosocial Rehabilitation, 2020)
To solve a number of practical problems associated with the movement of particles in a fluid flow, it becomes necessary to search for the nature of the movement of particles, taking into account a number of factors. Such tasks are gaining relevance when irrigation with a flexible hose in the conditions of Uzbekistan. Since the Amu Darya and Syr Darya rivers are the source of irrigated water, they bring a large amount of suspended particles in the water stream with water. In this research paper, we consider the motion of particles in flows, taking into account the attached mass. When the concentration of dispersed particles is insignificant, the mutual influence of the particles is negligible, and the movement of each particle in the liquid can be considered as occurring regardless of the presence of other particles. Therefore, the results that will be obtained for the case of movement of a single particle in a liquid are applicable. This makes it possible to study the laws of particle behavior based only on the equation for particles. Here, the behavior of particles is studied, taking into account the influence of the added mass effect and the Saffman forces. According to the results of the study in the conditions of particle motion in an upward flow, the effect of the attached mass effect is comparable to the Stokes hydrodynamic force at moderate. It is established that the separation of the Safman force from the Stokes force depends on the dimensionless parameter. The results show that for currents, the effect of the attached mass significantly affects the regime of particle flow in the water stream.